2022
DOI: 10.3390/life12122087
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Patients with Cystic Fibrosis: What We Know So Far

Abstract: Respiratory infections are the most common and most frequent diseases, especially in children and the elderly, characterized by a clear seasonality and with an incidence that usually tends to decrease with increasing age. These infections often resolve spontaneously, usually without the need for antibiotic treatment and/or with the possible use of symptomatic treatments aimed at reducing overproduction of mucus and decreasing coughing. However, when these infections occur in patients with weakened immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…CF patients also take precautions to prevent the spread of infection, including self-isolation, which probably contributes to the low occurrence of SARS-CoV-2 infection in this population (Bezzerri et al, 2020 ; Biondo et al, 2022 ). The Cystic Fibrosis Center in Parma endorsed self-isolation measures, including hand hygiene, sporting face masks, and remote verbal exchange, to reveal and avoid group activities throughout the pandemic period in Italy.…”
Section: Epidemiological and Clinical Outcomes Of Sars-cov-2 In Cf Pa...mentioning
confidence: 99%
“…CF patients also take precautions to prevent the spread of infection, including self-isolation, which probably contributes to the low occurrence of SARS-CoV-2 infection in this population (Bezzerri et al, 2020 ; Biondo et al, 2022 ). The Cystic Fibrosis Center in Parma endorsed self-isolation measures, including hand hygiene, sporting face masks, and remote verbal exchange, to reveal and avoid group activities throughout the pandemic period in Italy.…”
Section: Epidemiological and Clinical Outcomes Of Sars-cov-2 In Cf Pa...mentioning
confidence: 99%
“…Viral infections could have important effects on lung disease in pwCF, therefore, these patients were expected to be at increased risk of developing severe SARS-CoV-2 infections. However, several reports have demonstrated that worse outcomes did not occur in pwCF (Mathew et al, 2021;Biondo et al, 2022). A multinational cohort study of 40 individuals with CF identified an incidence of COVID-19 in pwCF of 0.07% compared to 0.15% in the general population (Cosgriff et al, 2020).…”
Section: Sars-cov-2 In Cystic Fibrosis Patients: Epidemiologymentioning
confidence: 99%
“…While the mechanisms by which HIV reactivates latent TB are known, the impact of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV) infection on latent TB is less clear [ 54 ]. SARS-CoV is a novel coronavirus that emerged in Wuhan, China, in December 2019 and caused the pandemic respiratory disease known as coronavirus disease 19 (COVID-19) [ 83 ]. COVID-19 was the fifth leading cause of death worldwide, and in the three years since the start of the pandemic, COVID-19 has killed more than 7.3 million people worldwide [ 84 ].…”
Section: Effects Of Sars-cov-2 Infection On Latent Tbmentioning
confidence: 99%